Low temperature oxidation behaviour of steel in molten alkali metal salts - Mohammed Misbahul, Amin (Kolej Universiti Sains dan Teknologi Malaysia, 2009)
Organized by Kolej Universiti Sains dan Teknologi Malaysia, 24th-25th March 2002 at Terengganu.